From occupation to cooperation : the United States and United Germany in a changing world order - Muller, Steven; American Assembly (Norton, 1992)
The relations between Germany and America have been central to world affairs since America emerged victorious in World War II. During the Cold War, West Germany's closeness and dependence on the United States was essential in defeating Communism. Now a reunified Germany has emerged once again as a dominant power in Europe. What shape will the pivotal U.S.-Germany relationship take in the years ahead? Where do the two countries' economic and security interests overlap, and where do they diverge? Will Germany's growing independence from the United States lead to increased rivalry between the two countries? Or will the emphasis be on sharing responsibilities in a partnership that will be a keystone of international order? In this new collection of essays, a joint German-American effort sponsored by the American Assembly and Atlantik-Brucke, leading voices from both countries provide their views on what will unite and what will divide the United States and Germany in the 1990s.